2018
DOI: 10.2147/ott.s158570
|View full text |Cite
|
Sign up to set email alerts
|

Evolving role of neurokinin 1-receptor antagonists for chemotherapy-induced nausea and vomiting

Abstract: To examine pharmacologic and clinical characteristics of neurokinin 1 (NK1)-receptor antagonists (RAs) for preventing chemotherapy-induced nausea and vomiting (CINV) following highly or moderately emetogenic chemotherapy, a literature search was performed for clinical studies in patients at risk of CINV with any approved NK1 RAs in the title or abstract: aprepitant (capsules or oral suspension), HTX019 (intravenous [IV] aprepitant), fosaprepitant (IV aprepitant prodrug), rolapitant (tablets or IV), and fixed-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 96 publications
(234 reference statements)
0
9
0
2
Order By: Relevance
“…Rolapitant IV contains the synthetic surfactant polyoxyl 15 hydroxystearate , and HTX‐019 (IV aprepitant) contains potentially allergenic excipients including egg lecithin, soybean oil, and ethanol but does not contain either polysorbate 80 or synthetic surfactants . Unlike these IV NK 1 RAs, the IV NEPA combination solution does not require any surfactant, emulsifier, or solubility enhancer and contains no allergenic excipients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolapitant IV contains the synthetic surfactant polyoxyl 15 hydroxystearate , and HTX‐019 (IV aprepitant) contains potentially allergenic excipients including egg lecithin, soybean oil, and ethanol but does not contain either polysorbate 80 or synthetic surfactants . Unlike these IV NK 1 RAs, the IV NEPA combination solution does not require any surfactant, emulsifier, or solubility enhancer and contains no allergenic excipients .…”
Section: Discussionmentioning
confidence: 99%
“…In general, the NK 1 RAs as a class are considered safe and well tolerated . However, hypersensitivity reactions and infusion‐site AEs have been associated with fosaprepitant, most likely due to the polysorbate 80 surfactant .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, scientific literature has provided good evidence on the effectiveness and safety of netupitant-palonosetron combination in both HEC and MEC settings (59)(60)(61)(62). The NCCN guideline recommends NK1 RA to be added to a 5-HT3/dexamethasone regimen for patients receiving MEC anticancer therapy who have additional risk factors, or previous treatment failure with the two-drug regimen.…”
Section: Nk1 Receptor Antagonistsmentioning
confidence: 99%
“…Aprepitant is a neurokinin-1 (NK-1) RA that functions in both the gut and the central nervous system by antagonizing the interaction of substance P (chemotherapyrelated increase) and NK-1 receptors to prevent CINV (7). Some clinical trials have suggested that adding aprepitant (ADH) to DH has achieved excellent effects (8).…”
Section: Introductionmentioning
confidence: 99%